PENGARUH MEDIA DIORAMA TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPAS MATERI FOTOSINTESIS KELAS IV - Panggasia Gagasi, Arjuliana; Oktavia, Wahyuni; Wirawan, Gunta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to: 1) determine the differences in learning outcomes between the experimental class and the control class; 2) determine the effect of diorama media on the learning outcomes of fourth-grade students in IPAS learning on photosynthesis material at SDN 52 Singkawang. This research was conducted at SDN 52 Singkawang. The type of research used was quantitative research with a quasi-experimental method in the form of a Non-Equivalent Control Group Design. The population of this study consisted of all fourth-grade students of SDN 52 Singkawang in the 2025/2026 academic year, totaling 40 students. The sample of this study consisted of class IV A as the experimental class and class IV B as the control class. Data collection techniques used learning outcome tests in the form of multiple-choice questions. Data analysis techniques included normality tests, homogeneity tests, independent sample t-tests, and effect size tests. The results of the study showed: 1) there were differences in learning outcomes between the experimental class and the control class. Based on the independent sample t-test results, the calculated t value was greater than the t table value, indicating that Hₐ was accepted and H₀ was rejected. 2) Diorama media had a high effect on the IPAS learning outcomes of fourth-grade students at SDN 52 Singkawang who received treatment using diorama media, with the effect size result categorized as high. Therefore, it can be concluded that diorama media has an effect on students’ IPAS learning outcomes on photosynthesis material for fourth-grade students at SDN 52 Singkawang. Keywords: learning outcomes, IPAS, diorama media, photosynthesis